ANALISIS HUKUM ISLAM TERHADAP KERJASAMA BAGI HASIL DALAM USAHA COFFEE SHOP PEABERY DI KECAMATAN LOWOKWARU KOTA MALANG - Fikri Ainul Yakin (Journal of Islamic Business Law, 2022)
This study aims to determine the practice of profit sharing in the coffee shop peabery and to find out the analysis of Islamic law on the cooperation carried out by shabihul mal and mudharib. This research uses empirical judirs research with a sociologic approach and a conceptual approach. The results showed that, 1) the profit sharing cooperation carried out by shahibul mal and mudharib was carried out using an oral or unwritten agreement, where this was due to the kinship (friendship) between shabibul mal and mudharib. In the agreement, the rights and obligations are regulated verbally, among others, the percentage of shahibul mal is 50% and mduharib 50% as business managers. In the Mudharib agreement also has an obligation to provide net profit as a form of profit sharing of 25% to Shabihul Mal every month, but in practice Mudharib experiences a forcemajeur, namely the COVID-19 pandemic which causes the business to not run well; 2) In the concept of Islamic law, the sharing of proceeds between shahibul mal and udharib is in accordance with the terms of the mudaraba agreement, but in practice it cannot run smoothly due to the COVID-19 pandemic which in a legal context is considered a forcemajeur.